1997
DOI: 10.1038/nm0697-678
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte deactivation in septic patients: Restoration by IFN-γ treatment

Abstract: Neutralization of proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-alpha) or interleukin-1 (IL-1), decreases mortality in several animal models of sepsis. However, recent clinical trials did not show an unequivocal improvement in survival. In contrast to animals, which succumb to shock during the first 72 hours, we found that many patients die much later with signs of opportunistic infections accompanied by downregulation of their monocytic HLA-DR expression and reduced ability to produce li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
781
4
27

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,069 publications
(867 citation statements)
references
References 15 publications
44
781
4
27
Order By: Relevance
“…It has recently been suggested that patients which succumb to septic shock after 72 h have similar clinical signs of endotoxin tolerance, and it has also been determined that the treatment of septic patients with IFN-g restored both deficient HLA-DR expression and LPS-induced TNF-a secretion in vitro [14]. All these data strongly suggest that more detailed studies on the mechanisms involved in tolerance to LPS would be beneficial for the management of sepsis or septic shock.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has recently been suggested that patients which succumb to septic shock after 72 h have similar clinical signs of endotoxin tolerance, and it has also been determined that the treatment of septic patients with IFN-g restored both deficient HLA-DR expression and LPS-induced TNF-a secretion in vitro [14]. All these data strongly suggest that more detailed studies on the mechanisms involved in tolerance to LPS would be beneficial for the management of sepsis or septic shock.…”
Section: Introductionmentioning
confidence: 95%
“…Despite the fact that host mechanisms responsible for LPS tolerance are not well understood, they seem to be crucial for patients with sepsis [3]. In fact, deactivation of monocytes in these late-stage sepsis patients, who die much later with signs of opportunistic infections, is accompanied by down-regulation of HLA-DR expression, loss of antigen-presenting capacity, and a profound reduction in their ability to produce LPS-induced TNF-a in vitro [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…While a normal monocyte will produce copious amounts of TNFα when exposed to LPS, an immunoparalyzed monocyte will not [28][29][30][31][32][33]. This approach suffers from a lack of standardization across investigators.…”
Section: Diagnosis and Quantification Of Immunoparalysismentioning
confidence: 99%
“…This state of sepsis-induced immunosuppression is triggered and supported by elevated levels of endotoxin and anti-inflammatory cytokines, characterised by a functional failure of innate and adaptive immunity [4], and is associated with increased mortality from sepsis [7,8]. Data from recent immunomodulatory trials show that this condition can be reversed by both immunostimulation [9][10][11] or reduction of inhibitory factors [12].…”
mentioning
confidence: 99%